(3JHUjQ GdefJHg HJMQjQ GdeTJHg (B( (3ddPgHi (B)s - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3eMeO Hf eMeO Hf eMeO GdZQGHjdi GdSGdei s)
(3ChdgG (B:s
(3GdMeO ddg LGeY GdfGS Gdjhe dGQjH ajg GdN s
(3BNQgG (B:s
(3MQQJg ai eOI BNQgG (B17 (3LeGOi SfI (B816 (3g` hgPg eShOI GdcJGH hdjS di ajg Shi MSf GdJdNjU GdeDJi HGdebUhO eY GdGNJUGQ djTGQc ai GdKhGH ef GdQMje GdhgGH SHMGfg hJYGdi s
(3YdjgG NW JhbjY eMeO Hf GdTMfg SfI (B864 (3hNW hdOg YHO Gddg SfI (B877(3g`s
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B68 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B34 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs